Normal-temperature preparation method of ultra-narrow emission spectrum perovskite quantum dot composite material

By induced the growth of perovskite quantum dots at room temperature using wide bandgap nanocrystals to form an assembled composite structure, the problem of the difficulty in preparing ultra-narrow emission spectral green light perovskite quantum dot materials with a half-maximum full width of less than 15 nanometers is solved, and efficient room temperature synthesis is achieved, meeting the needs of ultra-narrow emission spectra.

CN119736084APending Publication Date: 2025-04-01TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411919431.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

It is difficult to prepare ultra-narrow emission spectral green light perovskite quantum dot materials with a half-maximum full width less than 15 nanometers at room temperature.

Method used

The growth of perovskite quantum dots is induced at room temperature by using wide bandgap nanocrystals (such as BN or AlN nanocrystals) to form an assembled composite structure of perovskite quantum dots and wide bandgap nanocrystals, and the preparation of ultra-narrow emission spectrum is achieved.

Benefits of technology

Perovskite quantum dot composite material with a half-maximum full width below 15 nanometers was successfully prepared at room temperature. The half-maximum full width can reach 14.4 nanometers, meeting the needs of ultra-narrow emission spectrum. The method is simple and has industrial promotion value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736084A_ABST
    Figure CN119736084A_ABST
Patent Text Reader

Abstract

The invention relates to a normal-temperature preparation method of an ultra-narrow emission spectrum perovskite quantum dot composite material. The method comprises the following steps: firstly, mixing wide bandgap nanocrystals with a high-polarity solvent (such as N, N-dimethylformamide and the like) to prepare a wide bandgap nanocrystal solution; respectively mixing with perovskite quantum dot reaction precursors (such as CsBr, PbBr2 powder and the like) to prepare a reaction precursor solution; and mixing the reaction precursor solution, organic acid, organic amine and the like, and then adding a reverse polar solvent to form a precipitate, thereby preparing the perovskite quantum dot composite material with the ultra-narrow emission spectrum. The perovskite quantum dot composite material with the full width at half maximum of 15 nanometers or below can be prepared at normal temperature, and the minimum full width at half maximum can reach 14.4 nanometers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano fluorescent materials, and specifically relates to a room-temperature preparation method of a perovskite quantum dot composite material with an ultra-narrow emission spectrum. Background Art

[0002] Perovskite quantum dots have attracted much attention in the fields of ultra-high-definition display, solar cells, photoelectric detection, etc. due to their narrow emission spectrum, adjustable full visible spectrum, high light absorption, and solution preparation. Among them, ultra-narrow emission spectrum is a key requirement for the application of ultra-high-definition display and emerging quantum light source technology. Compared with CdSe and InP system quantum dots, perovskite quantum dots (such as CsPbBr3 perovskite quantum dots) have a narrower emission spectrum, especially in the green light band, where the half-width at half maximum can be less than 20 nanometers. However, it is very difficult to achieve ultra-narrow emission of perovskite quantum dots with a full width at half-maximum of the green light spectrum below 15 nanometers.

[0003] Factors that affect the full width at half maximum of perovskite quantum dots include crystal size uniformity, composition uniformity, surface and core defects, and strong quantum confinement, so it is difficult to form a simple preparation method to achieve its ultra-narrow emission spectrum. At present, only theoretical calculations have confirmed that perovskite quantum dots can achieve overload emission under strong quantum confinement, and their spectrum full width at half maximum can be less than 15 nanometers (see Nat. Commun. 2022, 13 (1), 2587.), but it is difficult to prepare green perovskite quantum dots with ultra-narrow emission spectrum and full width at half maximum less than 15 nanometers in experiments.

[0004] Therefore, there is an urgent need to develop green light perovskite quantum dot materials and preparation methods that can achieve ultra-narrow emission spectra. Summary of the invention

[0005] The purpose of the present invention is to provide a room temperature preparation method for ultra-narrow emission spectrum perovskite quantum dot composite materials in view of the shortcomings of the current technology. The method first mixes wide bandgap nanocrystals with high polarity solvents (such as N, N-dimethylformamide, etc.) to prepare a wide bandgap nanocrystal solution; then mixes with perovskite quantum dot reaction precursors (such as CsBr, PbBr2 powder, etc.) to prepare a reaction precursor solution; mixes the reaction precursor solution, organic acid (such as oleic acid, divaleric acid, etc.), and organic amine (oleylamine, etc.), and then adds a reverse polarity solvent to form a precipitate, thereby preparing a perovskite quantum dot composite material with an ultra-narrow emission spectrum. The present invention can prepare a perovskite quantum dot composite material with a half-peak full width of less than 15 nanometers at room temperature, and the narrowest half-peak full width can reach 14.4 nanometers.

[0006] The technical solution of the present invention is:

[0007] A method for preparing a perovskite quantum dot composite material with an ultra-narrow emission spectrum at room temperature, the method comprising the following steps:

[0008] 1) The first step is to prepare a wide bandgap nanocrystal solution

[0009] One of the following two methods:

[0010] Method 1: at room temperature, solvent A and solvent B are mixed and stirred for 0.1-1 hour to obtain solvent C; wide bandgap nanocrystals are added to solvent D and stirred for 0.1-10 hours to obtain solution E; solution E is mixed with solvent C and stirred for 0.1-5 hours to obtain a wide bandgap nanocrystal solution;

[0011] Wherein, the volume ratio of solvent A:solvent B=1:(0.1-5); the volume ratio of solution E:solvent C=1:(0.1-5);

[0012] Alternatively, in method 2, at room temperature, wide bandgap nanocrystals are added to solvent D and stirred for 0.1-10 hours to obtain solution E; solution E is mixed with solvent A and stirred for 0.1-3 hours to obtain a wide bandgap nanocrystal solution;

[0013] Wherein, the volume ratio of solution E:solvent A=1:(0.1~5);

[0014] In the above two methods, solvent A and solvent D are the same or different, and are N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone or N-methylpyrazoline, and solvent B is terpinene, toluene, xylene, and ethanol; the concentration of wide bandgap nanocrystals in solution E is 0.01-5M;

[0015] The wide bandgap nanocrystals are specifically boron nitride nanocrystals or aluminum nitride nanocrystals, which are commercially available or obtained according to a public preparation method.

[0016] 2) The second step is to prepare the quantum dot composite material precursor solution

[0017] One of the following two methods:

[0018] Method 1: Add lead halide and cesium halide to a wide bandgap nanocrystal solution to obtain solution F and solution G, then mix the two and stir for 0.1-7 hours to obtain a first mixed solution, then add organic amine and organic acid and stir for 0.1-5 hours to obtain a quantum dot composite material precursor solution;

[0019] Wherein, in the first mixed solution, the volume ratio of solution F:solution G=1:(1-5); the volume ratio of the organic acid to the first mixed solution is (0.01-1):1; the volume ratio of the organic amine to the first mixed solution is (0.005-1):1;

[0020] Alternatively, in method 2, cesium halide, bismuth halide and chitosan are added to a wide bandgap nanocrystal solution to obtain solution H, solution I and solution J, and then the three are mixed and stirred for 0.1-7 hours to obtain a second mixed solution, and then organic amine and organic acid are added and stirred for 0.1-5 hours to obtain a quantum dot composite material precursor solution;

[0021] Wherein, in the second mixed solution, the volume ratio of solution H:solution I:solution J=1:(1-7):(1-5); the volume ratio of the organic acid to the second mixed solution is (0.01-1):1; the volume ratio of the organic amine to the second mixed solution is (0.005-1):1;

[0022] The concentrations of solution F, solution G, solution H, solution I, and solution J are all 0.02 to 1 M;

[0023] The lead halide is one or more of lead bromide, lead chloride and lead iodide;

[0024] The cesium halide is one or more of cesium bromide, cesium chloride and cesium iodide;

[0025] The bismuth halide is one or more of bismuth bromide, bismuth chloride and bismuth iodide;

[0026] The chitosan solute is one or both of hydroxy chitosan and carboxyl chitosan;

[0027] The organic acid is one or both of oleic acid and divaleric acid;

[0028] The organic amine is one or both of oleylamine and octadecylamine.

[0029] 3) The third step is to prepare ultra-narrow emission perovskite quantum dot composite materials

[0030] At room temperature and in air atmosphere, under stirring, the quantum dot composite material precursor solution obtained in the second step is added dropwise to the solvent N, and stirred for 0.1-6 hours to obtain a quantum dot composite material solution; then the solvent P is added to the quantum dot composite material solution, mixed evenly, and centrifuged to obtain a precipitate, which is an ultra-narrow emission perovskite quantum dot composite material;

[0031] Wherein, the volume ratio of the quantum dot composite material precursor solution to the solvent N is (0.05-1):1, and the volume ratio of the quantum dot composite material solution:solvent P is 1:(0.1-1);

[0032] The solvent N is toluene, xylene, ethanol, methanol or isopropanol; the solvent P is ethyl acetate, methyl acetate, methyl formate or ethyl formate.

[0033] The stirring speed in steps (1), (2) and (3) is 100-600 revolutions per minute.

[0034] The essential features of the present invention are:

[0035] The present invention induces the growth of perovskite quantum dots by wide bandgap nanocrystals (such as BN nanocrystals, AlN nanocrystals, etc.) at room temperature to form an assembled composite structure of perovskite quantum dots and wide bandgap nanocrystals, thereby achieving a half-maximum full width of the emission spectrum of the prepared green light perovskite nanocrystals of less than 15 nanometers.

[0036] The beneficial effects of the present invention are:

[0037] In the present invention, the introduced "wide bandgap nanocrystals" can be assembled onto the surface of quantum dots at room temperature during the growth process of perovskite quantum dots; since wide bandgap nanocrystals (such as boron nitride and aluminum nitride) have a wide bandgap, they can enhance the quantum confinement effect on perovskite quantum dots, thereby effectively reducing the half-maximum full width of the emission spectrum of perovskite quantum dots.

[0038] Therefore, the preparation method described in the present invention uses wide bandgap nanocrystals to induce the growth of perovskite quantum dots at room temperature. Through the strong quantum confinement effect of the wide bandgap material, perovskite quantum dots with an ultra-narrow emission spectrum with a half-width at half maximum of less than 15 nanometers (the narrowest half-width can reach 14.4 nanometers) can be prepared; the prepared green light CsPbBr3 / BN perovskite quantum dot complex can achieve the saturated green color in the Rec.2020 color gamut display standard, and can effectively address the problem of green color point deviation in wide color gamut display; this method adopts a room temperature synthesis process, which is simple and has industrial promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The morphology of the composite material prepared in Example 1 and its comparative sample; wherein, Figure 1 (a) shows the morphology and lattice spacing of wide bandgap boron nitride nanocrystals used in the preparation method of Example 1; Figure 1 (b) shows the morphology and lattice spacing of CsPbBr3 quantum dots prepared in Comparative Example 1; Figure 1 (c) Transmission electron microscopy morphology of the prepared CsPbBr3 / BN composite material and the lattice spacing at the interface of the two nanomaterials;

[0040] Figure 2 This is an energy spectrum test diagram of the element types contained in the perovskite quantum dot composite material prepared in Example 1;

[0041] Figure 3 The photoluminescence spectra of the material prepared in Example 1 and its comparative sample include the full width at half maximum; wherein the dotted line is the CsPbBr3 perovskite quantum dots without the addition of boron nitride (BN) nanocrystals, and the solid line is the CsPbBr3 / BN perovskite quantum dot composite material after the introduction of boron nitride (BN) nanocrystals;

[0042] Figure 4 A comparison of the green light color point of the perovskite composite material prepared in Example 1 with the saturated green color point in the Rec.2020 color gamut standard;

[0043] Figure 5 This is a transmission electron microscope morphology image of the perovskite composite material prepared in Example 2;

[0044] Figure 6 The element types and distribution of the perovskite composite material prepared in Example 2;

[0045] Figure 7 This is a photoluminescence spectrum of the perovskite composite material prepared in Example 2, including the full width at half maximum. DETAILED DESCRIPTION

[0046] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0047] The preparation materials of the wide bandgap nanocrystals and perovskite quantum dots involved in the present invention are all known materials and can be commercially available or prepared.

[0048] Example 1: Preparation of CsPbBr3 / BN saturated green light quantum dot composite material with ultra-narrow emission spectrum

[0049] The first step is the preparation of boron nitride nanocrystal solution.

[0050] At room temperature, 1 mL of N,N-dimethylformamide was mixed with 0.1 mL of terpinene and stirred for 30 minutes to obtain solution A; 2 mmol of boron nitride nanocrystals were dissolved in 1 mL of N,N-dimethylformamide and stirred for 30 minutes to obtain solution B; solution A was mixed with solvent B and stirred for 1 hour to obtain a boron nitride nanocrystal solution;

[0051] Step 2: Preparation of CsPbBr3 / BN composite precursor solution

[0052] At room temperature, 0.1 mmol of cesium bromide and 0.1 mmol of lead bromide were respectively dissolved in 1 mL of the above-mentioned boron nitride nanocrystal solution, and stirred at a speed of 500 revolutions per minute for 10 minutes. The above solutions were mixed and stirred at a speed of 300 revolutions per minute for 10 minutes, and then 0.1 mL of oleic acid and 0.1 mL of oleylamine were added, and stirred again at a speed of 800 revolutions per minute for 10 minutes to obtain a CsPbBr3 / BN composite material precursor solution;

[0053] The third step is to prepare ultra-narrow emission CsPbBr3 / BN perovskite quantum dot composite materials

[0054] At room temperature, the above CsPbBr3 quantum dot composite material precursor solution was added dropwise into 10 mL of xylene while stirring at 300 rpm, and vigorously stirred at 500 rpm for 30 minutes to obtain a CsPbBr3 / BN perovskite quantum dot composite material solution; 5 mL of the composite material solution was taken and 1 mL of ethyl acetate was added to mix evenly, and then centrifuged at 8000 rpm for 5 minutes to obtain a precipitate, which is an ultra-narrow emission CsPbBr3 / BN saturated green light quantum dot composite material.

[0055] Comparative Example 1: Preparation of CsPbBr3 quantum dots

[0056] The first step is to prepare the CsPbBr3 quantum dot precursor solution

[0057] The other steps are the same as the second step of Example 1, except that the "boron nitride nanocrystal solution" is changed to N,N-dimethylformamide; finally, a CsPbBr3 quantum dot precursor solution is obtained;

[0058] The second step is to prepare CsPbBr3 quantum dots

[0059] The other steps are the same as the third step of Example 1, except that the "CsPbBr3 quantum dot composite material precursor solution" is changed to "CsPbBr3 quantum dot precursor solution"; finally, a CsPbBr3 quantum dot comparison sample is obtained.

[0060] Example 1 The material obtained by the method of the present invention is shown in the following figure by transmission electron microscopy (Talos F200X, FEI). Figure 1 As shown. Among them, Figure 1 (a) is a morphology image of the boron nitride nanocrystals used in Example 1. The boron nitride nanocrystals used are quasi-circular in shape, and the lattice spacing is 0.24 nanometers; Figure 1 (b) is a morphology of CsPbBr3 quantum dots in comparative example 1, which exhibit a cubic structure with a lattice spacing of 0.29 nanometers; Figure 1 (c) is the CsPbBr3 / BN composite material prepared in Example 1. The composite material is an assembly structure of boron nitride nanocrystals (quasi-circular structure) and CsPbBr3 quantum dots (cubic structure); at the same time, the 0.24 nanometer lattice spacing of the boron nitride nanocrystals and the 0.29 nanometer lattice spacing of the CsPbBr3 quantum dots on both sides of the assembly interface respectively correspond to the assembly of the two nanostructures. The CsPbBr3 / BN composite material prepared in Example 1 was characterized by energy spectrum using the above-mentioned transmission electron microscope, as shown in FIG. Figure 2 As shown in the figure, it can be found that the prepared material contains Cs, Pb, Br, B, and N elements, which further proves the composition of the composite material. The photoluminescence spectrum of the obtained material is characterized by a spectrometer (USB2000+, OceanOptics). Figure 3 As shown, the dotted line is the photoluminescence spectrum of CsPbBr3 perovskite quantum dots without adding boron nitride (BN) nanocrystals, and the solid line is the photoluminescence spectrum of CsPbBr3 / BN perovskite quantum dot composite material after introducing boron nitride (BN) nanocrystals; the CsPbBr3 / BN composite material obtained by the method of the present invention in Example 1 has an emission peak at 530 nanometers and a half-maximum full width of 14.4 nanometers. Compared with the control sample (half-maximum full width 26 nanometers), its spectrum is greatly narrowed, achieving an ultra-narrow emission below 15 nanometers. The green light color point of the material obtained in Example 1 was characterized by a spectral illuminance meter (SPIC-300), as shown in FIG. Figure 4 As shown, by comparison, the color point of the CsPbBr3 / BN perovskite quantum dot composite material almost coincides with the saturated green color point under the Rec.2020 standard, while the color point of the comparative sample CsPbBr3 quantum dots shows an obvious deviation. In summary, the perovskite quantum dot composite material prepared by the method of the present invention at room temperature has ultra-narrow emission and saturated green light characteristics.

[0061] Example 2: Preparation of Cs3Bi2Br9 / AlN quantum dot composite material with ultra-narrow emission spectrum

[0062] The first step is the preparation of aluminum nitride nanocrystal solution

[0063] At room temperature, 3 mmol of aluminum nitride nanocrystal solution was added to 1 mL of N,N-dimethylformamide, and stirred at a speed of 500 revolutions per minute for 30 minutes; and 0.5 mL of dimethyl sulfoxide was added thereto, and stirred at a speed of 500 revolutions per minute for 10 minutes; to obtain an aluminum nitride nanocrystal solution;

[0064] Step 2: Preparation of Cs3Bi2Br9 / AlN composite material precursor solution

[0065] At room temperature, 0.1 mmol cesium bromide, 0.1 mmol bismuth bromide and 0.1 mL chitosan were respectively dissolved in 1 mL of the above-mentioned aluminum nitride nanocrystal solution, and stirred at a speed of 500 revolutions per minute for 10 minutes. The above solutions were mixed and stirred at a speed of 300 revolutions per minute for 10 minutes. Then, 0.1 mL of divaleric acid and 0.1 mL of oleylamine were added, and stirred again at a speed of 800 revolutions per minute for 1 hour to obtain a Cs3Bi2Br9 / AlN composite material precursor solution.

[0066] The third step is the same as in Example 1.

[0067] Example 2 The material obtained by the method of the present invention is shown in the following figure by transmission electron microscopy (Talos F200X, FEI). Figure 5As shown in Figure 1, the smaller AlN nanocrystals are spherical and assembled with the larger Cs3Bi2Br9 quantum dots. The element scanning of the transmission electron microscope is shown in Figure 1. Figure 6 As shown in the figure, it can be found that the prepared Cs3Bi2Br9 / AlN quantum dot composite material shows a uniform distribution of Cs, Bi, Br, Al, and N elements, which further illustrates the assembly and compounding of Cs3Bi2Br9 quantum dots and AlN nanocrystals. The photoluminescence spectrum of the obtained material was characterized by a spectrometer (USB2000+, Ocean Optics). Figure 7 As shown, its emission peak is around 525 nanometers and its full width at half maximum is 14.46 nanometers, achieving ultra-narrow spectrum emission.

[0068] The above embodiments show that the method of the invention has the process of introducing wide bandgap nanocrystals and assembling them with perovskite quantum dots, and the preparation is carried out at room temperature, which effectively simplifies the synthesis process of ultra-narrow spectrum perovskite quantum dot composite materials and reduces costs; and realizes the room temperature synthesis of perovskite quantum dot composite materials with a half-width at half maximum of less than 15 nanometers.

[0069] Matters not covered by the present invention are known technologies.

Claims

1. A method for preparing a perovskite quantum dot composite material with an ultra-narrow emission spectrum at room temperature, characterized in that the method comprises the following steps: 1) Preparation of wide bandgap nanocrystal solution One of the following two methods: Method 1: at room temperature, solvent A and solvent B are mixed and stirred for 0.1-1 hour to obtain solvent C; wide bandgap nanocrystals are added to solvent D and stirred for 0.1-10 hours to obtain solution E; solution E is mixed with solvent C and stirred for 0.1-5 hours to obtain a wide bandgap nanocrystal solution; in, Volume ratio of solvent A:solvent B=1:(0.1-5); volume ratio of solution E:solvent C=1:(0.1-5); Alternatively, in method 2, at room temperature, wide bandgap nanocrystals are added to solvent D and stirred for 0.1-10 hours to obtain solution E; solution E is mixed with solvent A and stirred for 0.1-3 hours to obtain a wide bandgap nanocrystal solution; Wherein, the volume ratio of solution E:solvent A=1:(0.1~5); In the above two methods, solvent A and solvent D are the same or different, and are N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone or N-methylpyrazoline, and solvent B is terpinene, toluene, xylene, and ethanol; the concentration of wide bandgap nanocrystals in solution E is 0.01-5M; The wide bandgap nanocrystals are specifically boron nitride nanocrystals or aluminum nitride nanocrystals; 2) Preparation of quantum dot composite material precursor solution One of the following two methods: Method 1: Add lead halide and cesium halide to a wide bandgap nanocrystal solution to obtain solution F and solution G, then mix the two and stir for 0.1-7 hours to obtain a first mixed solution, then add organic amine and organic acid and stir for 0.1-5 hours to obtain a quantum dot composite material precursor solution; Wherein, in the first mixed solution, the volume ratio of solution F:solution G=1:(1-5); the volume ratio of the organic acid to the first mixed solution is (0.01-1):1; the volume ratio of the organic amine to the first mixed solution is (0.005-1):1; Alternatively, in method 2, cesium halide, bismuth halide and chitosan are added to a wide bandgap nanocrystal solution to obtain solution H, solution I and solution J, and then the three are mixed and stirred for 0.1-7 hours to obtain a second mixed solution, and then organic amine and organic acid are added and stirred for 0.1-5 hours to obtain a quantum dot composite material precursor solution; Wherein, in the second mixed solution, the volume ratio of solution H:solution I:solution J=1:(1-7):(1-5); the volume ratio of the organic acid to the second mixed solution is (0.01-1):1; the volume ratio of the organic amine to the second mixed solution is (0.005-1):1; The concentrations of solution F, solution G, solution H, solution I, and solution J are all 0.02 to 1 M; 3) Preparation of ultra-narrow emission perovskite quantum dot composite materials At room temperature and in air atmosphere, under stirring, the quantum dot composite material precursor solution obtained in the second step is added dropwise to the solvent N, and stirred for 0.1-6 hours to obtain a quantum dot composite material solution; then the solvent P is added to the quantum dot composite material solution, mixed evenly, and centrifuged to obtain a precipitate, which is an ultra-narrow emission perovskite quantum dot composite material; The volume ratio of the quantum dot composite material precursor solution to the solvent N is (0.05-1):1, and the volume ratio of the quantum dot composite material solution:solvent P is 1:(0.1-1).

2. The method for preparing the ultra-narrow emission spectrum perovskite quantum dot composite material at room temperature according to claim 1, characterized in that: The solvent N is toluene, xylene, ethanol, methanol or isopropanol; the solvent P is ethyl acetate, methyl acetate, methyl formate or ethyl formate.

3. The method for preparing the ultra-narrow emission spectrum perovskite quantum dot composite material at room temperature as claimed in claim 1, characterized in that: The lead halide is one or more of lead bromide, lead chloride and lead iodide; The cesium halide is one or more of cesium bromide, cesium chloride and cesium iodide; The bismuth halide is one or more of bismuth bromide, bismuth chloride and bismuth iodide; The chitosan solute is one or both of hydroxy chitosan and carboxyl chitosan.

4. The method for preparing the ultra-narrow emission spectrum perovskite quantum dot composite material at room temperature as claimed in claim 1, characterized in that: The organic acid is one or both of oleic acid and divaleric acid; The organic amine is one or both of oleylamine and octadecylamine.

5. The method for preparing the ultra-narrow emission spectrum perovskite quantum dot composite material at room temperature as claimed in claim 1, characterized in that: The stirring speed in steps 1), 2) and 3) is 100-600 revolutions per minute.

Citation Information

Cited By

  • Method for preparing perovskite quantum dots by utilizing nano instantaneous precipitation

    CN121022400A

  • A method for preparing perovskite quantum dots by using nano transient precipitation

    CN121022400B